Prevalence of Vitamin D Deficiency and the Association with Coffee Consumption among Female Employees of Imam Hossein Medical Center, Tehran, Iran - Giti Noghabaei; Maliheh Arab; Sara Payami; Nasim Nouri; Behnaz Ghavami; Behnaz Nouri; Roya Parkhideh (International Journal of Nutrition Sciences, 2025)
Background: Measurement of serum vitamin D levels can assist healthcare providers in the provision of appropriate advice and management for low vitamin D status. This study determined the prevalence of vitamin D deficiency and the association with coffee consumption among female employees in Tehran, Iran.Methods: Six hundred fifty-one female staff of Imam Hossein Medical Center, Tehran, Iran aged between 20 and 67 years were enrolled in a prospective cross-sectional study. Age, educational level, reproductive history, employment records and daily consumption of different types of food and beverages of all the participants were collected in a questionnaire. Serum level of 25-dihydroxy vitamin D was also measured.Results: Four-hundred out of 651 working staff (61.5%) demonstrated vitamin D deficiency, while 46.4% suffered from a severe deficiency. No significant link was found between serum vitamin D level and dietary consumption of meat, nuts, vegetables, fruit, salad, and tea; but coffee consumption was significantly associated with a lower vitamin D level. Longer employment duration could significantly reduce the risk of vitamin D deficiency by 5% per year. Calcium-vitamin D and multivitamin supplements significantly decreased the risk of deficiency by 53% and 52%, respectively.Conclusion: Vitamin D deficiency was highly prevalent among female employees of the medical center and was inversely associated with their age, duration of employment, and use of multivitamins and calcium-D supplements. Coffee drinking was correlated with a lower serum vitamin D level in the study population.